Quantitative Methods for Business Decision / With Cases: Sixth Edition - Lapin Lawrence L (Duxbury Press, 1994)
Preface, Introduction to Quantitative Methods for Decision Making, Probability Concepts, Probability Distributions and Expected Value and Sampling, Assessing Probabilities Through Judgement, Forecasting, Inventory Decisions With certain Factors, Inventory Decisions with Uncertain Factors, Linear Programming, Linear Programming Formulation and Computer Solution, Solving Linear Programs I: The Simplex Method, Solving Linear Programs II: Surplus and Artificial Variables, Shadow Prices and Duality in Linear Programming, Post-Optimality and Sensitivity Analysis in Linear Programming, The Transportation Problem, Integer Programming and the Branch-and-Bound Method, Goal Programming, Network Models in Linear Programming, Project Planning with PERT, Waiting Lines (Queues), Simulation, Basic Concepts of Decision Making, Decision Theory, Decision Making Using the Normal Distribution, Decision Making with Utility, Games and Interactive Decisions, Dynamic Programming, Index.
Preface, Introduction to Quantitative Methods for Decision Making, Probability Concepts, Probability Distributions and Expected Value and Sampling, Assessing Probabilities Through Judgement, Forecasting, Inventory Decisions With certain Factors, Inventory Decisions with Uncertain Factors, Linear Programming, Linear Programming Formulation and Computer Solution, Solving Linear Programs I: The Simplex Method, Solving Linear Programs II: Surplus and Artificial Variables, Shadow Prices and Duality in Linear Programming, Post-Optimality and Sensitivity Analysis in Linear Programming, The Transportation Problem, Integer Programming and the Branch-and-Bound Method, Goal Programming, Network Models in Linear Programming, Project Planning with PERT, Waiting Lines (Queues), Simulation, Basic Concepts of Decision Making, Decision Theory, Decision Making Using the Normal Distribution, Decision Making with Utility, Games and Interactive Decisions, Dynamic Programming, Index.